2015
DOI: 10.1016/j.physleta.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The quantum brachistochrone problem for an arbitrary spin in a magnetic field

Abstract: Please cite this article in press as: A.R. Kuzmak, V.M. Tkachuk, The quantum brachistochrone problem for an arbitrary spin in a magnetic field, Phys. Lett. A (2015), http://dx. Highlights• The Fubini-Study metrics of rotational manifolds of spin-s system are considered.• It is shown that they are spheres.• The brachistochrone problem for a spin-s system on rotational manifolds is examined. We consider quantum brachistochrone evolution for a spin-s system on rotational manifolds. Such manifolds are determined b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…As in the previous case, the best coincidence of the results with theoretical prediction we obtain for θ = π/2. Finally, substituting Hamiltonian (25) with initial state (23) into expression (10) we obtain…”
Section: Ising Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the previous case, the best coincidence of the results with theoretical prediction we obtain for θ = π/2. Finally, substituting Hamiltonian (25) with initial state (23) into expression (10) we obtain…”
Section: Ising Modelmentioning
confidence: 99%
“…The concept of a distance between quantum states in Hilbert space [1][2][3] has found its application in different fields of quantum mechanics related to the evolution of quantum systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], quantum entanglement [8,[20][21][22][23][24][25][26][27][28][29][30], quantum computations [31][32][33][34][35], etc. It was shown that the distance, which the quantum system passes during the evolution in the Hilbert space, is related to the integral of the uncertainty of energy that in turn defines the speed of evolution [4].…”
Section: Introductionmentioning
confidence: 99%
“…If the parameter χ is fixed then we have the manifold which contains all possible initials states. It has the geometry of a sphere with radius γ Ns/2 (for instance, see, [22,71,72]). Also it is easy to see that the manifolds with different certain φ have the same geometry.…”
Section: The Long-range Ising-type Modelmentioning
confidence: 99%
“…In our previous paper [4], we use the geometric characteristics such as curvature and torsion to study the quantum evolution. The geometry of quantum states in the evolution of a spin system was studied in [5,6]. In [7], the distance between quantum states was used for quantifying the entanglement of pure and mixed states.…”
Section: Introductionmentioning
confidence: 99%